2013
DOI: 10.1021/ac303609n
|View full text |Cite
|
Sign up to set email alerts
|

Directly Coupled High-Performance Liquid Chromatography–Accelerator Mass Spectrometry Measurement of Chemically Modified Protein and Peptides

Abstract: Quantitation of low-abundance protein modifications involves significant analytical challenges, especially in biologically important applications, such as studying the role of post-translational modifications in biology and measurement of the effects of reactive drug metabolites. 14C labeling combined with accelerator mass spectrometry (AMS) provides exquisite sensitivity for such experiments. Here, we demonstrate real-time 14C quantitation of high-performance liquid chromatography (HPLC) separations by liquid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…3739,54 Our findings show that Cys 34 is the principal nucleophile of albumin to react with all of these N -oxidized metabolites of PhIP, to form a putative sulfenamide, and more stable sulfinamide and sulfonamide linked adducts. 3739 Crystallography and NMR studies with human albumin have shown that the Cys 34 resides in a shallow crevice of the protein, 6062 but it is accessible to solvent. Moreover, the Cys 34 residue of albumin has an unusually low pKa value, 6.5 as compared to about 8.0 to 8.5 in many other proteins or peptides, 20,63 and it predominantly exists as the thiolate anion at physiological pH, which explains its reactivity towards N -oxidized PhIP metabolites and many other electrophiles.…”
Section: Discussionmentioning
confidence: 99%
“…3739,54 Our findings show that Cys 34 is the principal nucleophile of albumin to react with all of these N -oxidized metabolites of PhIP, to form a putative sulfenamide, and more stable sulfinamide and sulfonamide linked adducts. 3739 Crystallography and NMR studies with human albumin have shown that the Cys 34 resides in a shallow crevice of the protein, 6062 but it is accessible to solvent. Moreover, the Cys 34 residue of albumin has an unusually low pKa value, 6.5 as compared to about 8.0 to 8.5 in many other proteins or peptides, 20,63 and it predominantly exists as the thiolate anion at physiological pH, which explains its reactivity towards N -oxidized PhIP metabolites and many other electrophiles.…”
Section: Discussionmentioning
confidence: 99%
“…38,39 This data provides the first environmentally relevant human metabolic data following exposure to a defined ultra-low dose of a carcinogenic PAH. The data will be critical for ongoing and future evaluations of PBPK model predictions and human health risk assessments.…”
Section: Introductionmentioning
confidence: 99%
“…The group at Lawrence Livermore National Laboratory led by Ognibene and coworkers has developed a real-time moving wire interface (MWI) that appears highly promising [73,78–79]. The MWI was originally developed as an effluent monitor for liquid chromatography in the 1960s and later optimized and applied for liquid chromatograph/combustion isotope ratio mass spectrometry.…”
Section: New Technology: True Lc/ams Systemmentioning
confidence: 99%